2021
DOI: 10.1016/j.advms.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum CK-MB, COVID-19 severity and mortality: An updated systematic review and meta-analysis with meta-regression

Abstract: Objectives We conducted a systematic review and meta-analysis with meta-regression of creatine kinase-MB (CK-MB), a biomarker of myocardial injury, in COVID-19 patients. Methods We searched PubMed, Web of Science and Scopus, for studies published between January 2020 and January 2021 that reported CK-MB, COVID-19 severity and mortality (PROSPERO registration number: CRD42021239657). Results Fifty-five studies in 11,791 COVID-19 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…The serum troponin I was significantly increased only in severe cases. These results are in concordance with those of previous publications [ 39 , 40 , 41 , 42 ], which recommended that patients check cardiac markers at admission, which helps medical staff predict the severity of patients in the later stage, and these cardiac biomarkers in serum could act as prognostic biomarkers in COVID-19 patients. As stated by Li et al [ 40 ] and Sultan et al [ 43 ], the mechanisms of actions of COVID-19 to induce heart injury include specific binding to functional receptors on cardiomyocytes and immune-mediated myocardial injury.…”
Section: Discussionsupporting
confidence: 92%
“…The serum troponin I was significantly increased only in severe cases. These results are in concordance with those of previous publications [ 39 , 40 , 41 , 42 ], which recommended that patients check cardiac markers at admission, which helps medical staff predict the severity of patients in the later stage, and these cardiac biomarkers in serum could act as prognostic biomarkers in COVID-19 patients. As stated by Li et al [ 40 ] and Sultan et al [ 43 ], the mechanisms of actions of COVID-19 to induce heart injury include specific binding to functional receptors on cardiomyocytes and immune-mediated myocardial injury.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al found that elevated level of cardiac markers showed increased higher mortality than those normal serum levels [ 5 ]. Angelo Zinellu et al found that higher CK-MB concentrations were associated with the mortality and severe disease in COVID-19 patients [ 30 ]. But we found that CK-MB ( P = 0.363) and CK ( P = 0.489) had no significant difference in the prediction effect of the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies (46 studies) reported the impact of CI on mortality (Table 1) [5,12,15,17,18,20,[22][23][24]29,[31][32][33]35,39,40,[42][43][44][45][46][47][48][49][50][51][52][53][56][57][58][59][60][61][62][63][64][65][66][67]70,73,74,[76][77][78].…”
Section: Resultsmentioning
confidence: 99%